Pengaruh Lingkungan Kerja, Pengembangan Karir, dan Tunjangan Kinerja Terhadap Motivasi Kerja Karyawan (Pada PT. Bank Tabungan Negara (Persero) Tbk Cabang Kediri) - Yusiak Ciciniwayatul; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract This research was conducted with the aim of knowing the description of the work environment, career development, performance allowances, and employee motivation. And to analyze and find out the effect partially or simultaneously on the work environment, career development, and performance allowances on employee motivation.The population used in this study are all employees of PT. BTN (Persero) Tbk Kediri Branch. Determination of samples using the total sample method. Based on the criteria obtained 65 employees. The method of data collection uses a questionnaire, while the data analysis method uses validity test, reliability test, normality test, classic assumption test, multiple linear regression analysis with hypothesis testing using the F test and t test.The results of this study indicate that partially the work environment variables and performance allowance variables do not have an important effect on employee work motivation, while for career development variables partially have an important effect on employee work motivation. Simultaneously work environment variables, career development, and performance allowances have an important effect on employee work motivation. Keywords: Work Environment, Career Development, Performance Allowances, Work Motivation.